Analysis of the use of the P3SPD platform to improve the digital management competency of female employees in the ERA of budget efficiency policies - Safrida, Safrida; Supriadi, Supriadi; Leman, Dedi; Khaira, Imamul; Syah, Amirul; Susilawati, Evi; Hakiki, Agusnadi Al; Amri, Khairil; Siagian, Mora Alhady Asyar (Edelweiss Applied Science and Technology, 2025)
This study aims to analyze the effect of using the Digital Women’s Human Resource Development Training Platform (Platform Pelatihan Pengembangan SDM Perempuan Digital, P3SPD) on improving the digital management competencies of female employees at the Tanjungbalai City Education Office, particularly within the context of budget efficiency policies. A quantitative approach with an explanatory design was employed through a cross-sectional survey method. The research subjects consisted of the entire population of 28 female employees who participated in training via the P3SPD platform, selected using a saturated sampling technique. Data were collected through a validated closed-ended questionnaire using a 5-point Likert scale, supported by secondary data from the platform usage log. Data analysis was conducted using SPSS version 25, including classical assumption tests and simple linear regression analysis. The findings reveal that the use of P3SPD has a positive and significant effect on improving digital management competencies (β = 0.652; p = 0.008), contributing 23.9% to the variance, with the remainder influenced by other factors. Improved competencies include electronic document management, cloud-based digital collaboration, and digital document security.